Benzoic acid improves nutritional quality in lentil sprouts - Gaucin-Delgado, Alejandra; Márquez-Guerrero, Selenne Y.; Carballo Méndez, Fernando de Jesús; Moreno-Reséndez, Alejandro; Espinosa-Palomeque, Bernardo; Gaucin-Delgado, Jazmín M. (Revista Mexicana de Ciencias Agrícolas, 2024)
Sprouts are foods that have been winning consumers for their pleasant freshness and are used to accompany various dishes, both at home and in a large number of restaurants around the world. In addition, they represent a food of high nutritional quality since they are a source of minerals, vitamins, and bioactive compounds. The use of elicitors can improve the nutritional quality of these foods. In this study, five concentrations (0, 10-2, 10-3, 10-4, and 10-5 M) of benzoic acid were evaluated in lentil (Lens culinaris L.) sprouts. Biomass production, total soluble solids, total phenolic compounds, total flavonoids, and total antioxidant capacity were quantified. Elicitation with BA at low concentrations significantly improved the accumulation of DM and bioactive compounds; on the other hand, high concentrations significantly reduced these parameters. Elicitation with BA is a simple and efficient alternative to promote biomass production and induce the biosynthesis of bioactive compounds in lentil sprouts to obtain functional foods.